Management of locally advanced T3–4 glottic laryngeal carcinomas. Issue 7 (2nd July 2018) - Smee, R; Williams, J R; Kotevski, D P
Abstract: Objectives: To assess five-year local control and ultimate local control rates of patients treated for locally advanced T3–4 glottic carcinoma with surgery only, radiotherapy only, or surgery plus radiotherapy. Cancer-specific survival, overall survival and rates of malignancy development were also assessed. Methods: A retrospective review was conducted on patients from 1967 to 2015, with analysis of local control, ultimate local control, overall survival and cancer-specific survival performed using Kaplan–Meier and Cox regression. Results: Of 169 eligible patients, the majority (59 per cent) were treated with surgery plus radiotherapy, with laryngectomy being the most common surgical procedure. Local control and ultimate local control rates were higher with surgery only (94.1 per cent) and surgery plus radiotherapy (87.9 and 86.8 per cent respectively), compared to radiotherapy only (46.8 and 52.4 per cent) (both p < 0.001). Cancer-specific survival, overall survival and malignancy development did not differ between groups. Conclusion: Surgery, with or without radiotherapy, offers significantly higher five-year local control and ultimate local control for patients with advanced glottic carcinoma, compared to radiotherapy only.